PROSES PEMBUATAN BROSUR TPQ MADANI STUDI KASUS: YAYASAN MASYARAKAT MADANI INDONESIA BARU - Fadzar Rusghana; Syarifah Aini (CAHAYAtech, 2022)
The production of a brochure is of great importance in knowing and promoting an institution to the community. In the process of making a brochure has to understand the background, and understanding of the material so that it makes it eraser to determine the design concept. The problems of designing a brochure are not limited to the non-technical side, most of the failure to design it is due to the lack of technical understanding, the designer must understand it well from the technical or the non-technical side to the design process. Keywords:Making Brochure, Knowing and Promoting